Functional brain perfusion evaluation with Arterial Spin Labeling at 3 Tesla - Pimentel, Marco André Figueiredo (2013)
Dissertation submitted in Faculdade de Ciências e Tecnologia of Universidade Nova de Lisboa for the degree of Master of Biomedical Engineering